Digital Tools as Parental Support—A Study Protocol Describing Prospective Development and Exploration of Two Digital Tools for Parents - Bäckström, Caroline; Engström, Henrik; Knez, Rajna; Larsson, Margaretha (Frontiers in Digital Health, 2021)
Background: The access to digital tools for parents is increasing, and further exploration is needed to gain knowledge about parents’ experiences in using such tools, for example, when preparing for childbirth and parenthood. This study protocol describes a prospective study that will explore serious games as digital tools for parental support, and both parents’ and healthcare professionals’ views will be included. The objectives of the prospective study are to explore two different serious games: (1) Childbirth Journey (Swedish: Förlossningsresan), relating to pregnancy, childbirth and parenthood; and (2) Interplay (Swedish: Samspel), relating to parental couple relationships and parenthood. Methods: An intervention study will be conducted. The study will include four different sub-studies (A–D) with both qualitative and quantitative methods and a longitudinal design. Both parents (A, B and D) and healthcare professionals (C) will be included, and data will be collected through interviews (A–C) and repeated web-based questionnaires (D). Data will be analysed using phenomenography and qualitative content analysis (A–C), and descriptive and analytical analyses will be performed for comparisons and associations (D). Discussion: The value of monitoring and reporting on developments and trends in digital innovation for public health has been stipulated by the World Health Organization. The prospective study will contribute further knowledge about multidisciplinary development of digital tools as professional support for parents, as well as knowledge about parents’ and healthcare professionals’ experiences using digital tools concerning pregnancy, labour, parenthood and parental couple relationships. Trial: This study was retrospectively registered (02/10/2020) within the ISRCTN with ID: ISRCTN18017741. http://www.isrctn.com/ISRCTN18017741